It hurts ’cause you’re in my world now, bitch: Gothic features in the 1984 and 2010 versions of A Nightmare on Elm Street - Claudio Vescia Zanini (Ilha do Desterro)
This article aims to discuss the 1984 slasher film A Nightmare on Elm Street and its 2010 remake within a Gothic framework. The main hypothesis is that while both versions display Gothic traces in their imagery and structure, such as transgression and excesses (Botting, 2004), the monstrous character, the haunting return of the past, and the Terrible Place (Clover, 2015), the 2010 film capitalizes more efficiently on the interplay between appearance and reality by enhancing the importance of trauma in its plot. The proposal’s pertinence and originality rely on the juxtaposition of a consolidated framework (Gothic studies), a prolific horror cinema subgenre (slashers), and a recurrent tendency in contemporary cinema (remakes).